Sovereign credit default swap and bond markets' dynamics: evidence from the European debt crisis. (2018) - Tampakoudis, Ioannis A.; Subeniotis, Demetres N.; Kroustalis, Ioannis G.
This study investigates the sovereign credit market dynamics of the heavily indebted southern European countries, considering the dynamic relationship between credit default swap (CDS) and bond spreads. We employ a three-step econometric analysis, intending to shed light on whether the CDS spreads can trigger rises in bond spreads and on the relative efficiency of credit risk pricing in the CDS and bond spreads. The VECM analysis suggests that during an economic turbulence the CDS market leads the price discovery process in Portugal, Greece and Spain, while in Italy the Granger causality test indicates bilateral causality between CDS and bond spreads without identifying the leading market. Hence, an increase in the CDS spread may directly affect the sovereign cost of borrowing. Governments, investors and policy makers should place specific emphasis on the CDS market, since it constitutes the main source of information for sovereign credit risk.